A 14-bit digitally self-calibrated pipelined ADC with adaptive bias optimization for arbitrary speeds up to 40 MS - Iizuka, K.
This paper presents a 14-bit digitally self-calibrated pipelined analog-to-digital converter (ADC) featuring adaptive bias optimization. Adaptive bias optimization controls the bias currents of the amplifiers in the ADC to the minimum amount required, depending on the sampling speed, environment temperature, and power-supply voltage, as well as the variations in chip fabrication. It utilizes information from the digital calibration process and does not require additional analog circuits. The prototype ADC occupies an area of 0.5×2.3 mm2 in a 0.18-μm dual-gate CMOS technology; with a power supply of 2.8 V, it consumes 19.2, 33.7, 50.5, and 72.8 mW when operating at 10, 20, 30, and 40 MS/s, respectively. The peak differential nonlinearity (DNL) is less than 0.5 least significant bit (LSB) for all the sampling speeds with temperature variation up to 80°C. When operated at 20 MS/s with 1-MHz input, the ADC achieves 72.1-dB SNR and 71.1-dB SNDR.
Keywords: 0.18 micron; 14 bit; 19.2 mW; 2.8 V; 33.7 mW; 50.5 mW; 72.8 mW; Adaptive bias optimization; Analog-digital converter; Chip fabrication; Differential nonlinearity; Digital calibration process; Dual-gate CMOS technology; Environment temperature; Power-supply voltage; Sampling speed; Self-calibrated pipelined ADC